The combined impact of Type D personality and depression on cardiovascular events after acute myocardial infarction. Issue 4 (2nd March 2023) - Wang, Yini; Gao, Xueqin; Zhao, Zhenjuan; Li, Ling; Liu, Guojie; Tao, Hui; Yu, Xi; Yu, Bo; Lin, Ping
Abstract: Background: Type D personality and depression are the independent psychological risk factors for adverse outcomes in cardiovascular patients. The aim of this study was to examine the combined effect of Type D personality and depression on clinical outcomes in patients suffering from acute myocardial infarction (AMI). Methods: This prospective cohort study included 3568 patients diagnosed with AMI between February 2017 and September 2018. Type D personality and depression were assessed at baseline, while the major adverse cardiac event (MACE) rate (cardiac death, recurrent non-fatal myocardial infarction, revascularization, and stroke) and in-stent restenosis (ISR) rate were analyzed after a 2-year follow-up period. Results: A total of 437 patients developed MACEs and 185 had ISR during the follow-up period. The Type D (+) depression (+) and Type D (+) depression (−) groups had a higher risk of MACE [95% confidence interval (CI) 1.74–6.07] (95% CI 1.25–2.96) and ISR (95% CI 3.09–8.28) (95% CI 1.85–6.22). Analysis of Type D and depression as continuous variables indicated that the main effect of Type D, depression and their combined effect were significantly associated with MACE and ISR. Moreover, Type D (+) depression (+) and Type D (+) depression (−) emerged as significant risk factors for MACE and ISR in males, while only Type D (+) depression (+) was associated with MACE and ISR in female patients. Conclusions: These findings suggest that patients complicated with depression and Type D personality are at a higher risk of adverse cardiovascular outcomes. Individual assessments of Type D personality and depression, and comprehensive interventions are required.